Il Serventese del Dio d’Amore e il suo contesto letterario e editoriale - Lecco, Margherita (Cuadernos de Filología Italiana, 2007)
Subjects discussed includes material manuscripts and intertextual patterns of a short thirtheenth-century work fragmentary preserved in the Zibaldone da Canal (Venice, 1311) and in the Rime dei Memoriali Bolognesi (Bologna, 1309). A folk-motif (the ‘Purgatory of Cruel Beauties’) is seen as model that both set a pattern for individual successors in verse and provided the groundwerk for the interlace and amplification (the Novel of Nastagio degli Onesti, Decameron, VIII, 5).